Alkaline sphingomyelinase (NPP7) impacts the homeostasis of intestinal T lymphocyte populations - Alyamani, Manar; Kadivar, Mohammad; Erjefält, Jonas; Johansson-Lindbom, Bengt; Duan, Rui-Dong; Nilsson, Åke; Marsal, Jan (Frontiers in Immunology, 2023)
Background and aim: Alkaline sphingomyelinase (NPP7) is expressed by intestinal epithelial cells and is crucial for the digestion of dietary sphingomyelin. NPP7 also inactivates proinflammatory mediators including platelet-activating factor and lysophosphatidylcholine. The aim of this study was to examine a potential role for NPP7 in the homeostasis of the intestinal immune system. Methods: We quantified the numbers of B-lymphocytes, plasma cells, T-lymphocytes including regulatory T-lymphocytes (Tregs), natural killer cells, dendritic cells, macrophages, and neutrophils, in the small and large intestines, the mesenteric lymph nodes and the spleens of heterozygous and homozygous NPP7 knockout (KO) and wildtype (WT) mice. Tissues were examined by immunohistochemistry and stainings quantified using computerized image analysis. Results: The numbers of both small and large intestinal CD3+, CD4+, and CD8+ T-lymphocytes were significantly higher in NPP7 KO compared to WT mice (with a dose-response relationship in the large intestine), whereas Treg numbers were unchanged, and dendritic cell numbers reduced. In contrast, the numbers of CD3+ and CD4+ T-lymphocytes in mesenteric lymph nodes were significantly reduced in NPP7 KO mice, while no differences were observed in spleens. The numbers of B-lymphocytes, plasma cells, natural killer cells, macrophages, and neutrophils were similar between genotypes. Conclusion: NPP7 contributes to the regulation of dendritic cell and T-lymphocyte numbers in mesenteric lymph nodes and both the small and large intestines, thus playing a role in the homeostasis of gut immunity. Although it is likely that the downstream effects of NPP7 activity involve the sphingomyelin metabolites ceramide and spingosine-1-phosphate, the exact mechanisms behind this regulatory function of NPP7 need to be addressed in future studies.